Magnification endoscopy in the diagnostics of upper gastrointestinal tract diseases - Wasielica-Berger, Justyna; Piotrowska-Staworko, Grażyna; Baniukiewicz, Andrzej; Dąbrowski, Andrzej (Gastroenterology Review/Przegląd Gastroenterologiczny, 2010)
The newly developed high-resolution and magnification endoscopes offer features that allow discerning more mucosal details, especially mucosal surface structure and superficial vessels. This article summarizes the principles of magnification endoscopy with chromoendoscopy and discusses it’s possible clinical use. We describe magnified picture of normal esophagus, stomach and duodenum as well as most frequent pathologies of upper gastrointestinal tract.